Defining daptomycin resistance prevention exposures in vancomycin-resistant Enterococcus faecium and E. faecalis (2020)
Daptomycin is used off-label for enterococcal infections; however, dosing targets for resistance prevention remain undefined. Doses of 4 to 6 mg/kg of body weight/day approved for staphylococci are likely inadequate against enterococci due to reduced susceptibility. We modeled daptomycin regimens in vitro to determine the minimum exposure to prevent daptomycin resistance (Dapr ) in enterococci. Daptomycin simulations of 4 to 12 mg/kg/day (maximum concentration of drug in serum [Cmax] of 57.8, 93.9, 123.3, 141.1, and 183.7 mg/liter; half-life [t1/2] of 8 h) were tested against one Enterococcus faecium strain (S447) and one Enterococcus faecalis strain (S613) in a simulated endocardial vegetation pharmacokinetic/pharmacodynamic model over 14 days. Samples were plated on media containing 3 the MIC of daptomycin to detect Dapr . Mutations in genes encoding proteins associated with cell envelope homeostasis (yycFG and liaFSR) and phospholipid metabolism (cardiolipin synthase [cls] and cyclopropane fatty acid synthetase [cfa]) were investigated in Dapr derivatives. Dapr derivatives were assessed for changes in susceptibility, surface charge, membrane depolarization, cell wall thickness (CWT), and growth rate. Strains S447 and S613 developed Dapr after simulations of 4 to 8 mg/kg/day but not 10 to 12 mg/kg/day. MICs for Dapr strains ranged from 8 to 256 mg/liter. Some S613 derivatives developed mutations in liaF or cls. S447 derivatives lacked mutations in these genes. Dapr derivatives from both strains exhibited lowered growth rates, up to a 72% reduction in daptomycin-induced depolarization and up to 6-nm increases in CWT (P < 0.01). Peak/MIC and AUC0 –24/MIC ratios (AUC0 –24 is the area under the concentration-time curve from 0 to 24 h) associated with Dapr prevention were 72.1 and 780 for S447 and 144 and 1561 for S613, respectively. Daptomycin doses of 10 mg/kg/day may be required to prevent Dapr in serious enterococcal infections.